KANDUNGAN BAHAN AKTIF DAN TOKSISITAS TUMBUHAN HUTAN ASAL SULAWESI UTARA YANG BERPOTENSI SEBAGAI OBAT - Lis Nurrani; Julianus Kinho; Supratman Tabba (BRIN Publishing, 2014)
Utilization of germplasms as medical sources presents a form of traditional wisdom adopted by a particular community which is identical with a hereditary legacy. This paper deals descriptively with ethnobotany aspects of North Sulawesi community (Minahasa, Mongondow and Sangihe tribes) in utilizing natural bioresources from several forest plant species as traditional cancer-curing treatment, which was further proved scientifically through the identification of active ingredients contents and their efficacious toxicity using Brine Shrimp Lethality Test (BSLT) method. Scrutiny results revealed that the local community in North Sulawesi province has prevalently utilized particular portions (e.g. wood, bark, and leaves) of 14 forest plant species for cancer cure and other desease. The herbal extract from the bark of lawang (Cinnamomum cullilawan Bl) was identified containing alkaloids, while flavonoids was detected in the extract from consecutively lingkeube (Dischidia imbricata Steud) leaves, yantan (Blumea chinensis Dc) leaves, ketapang (Terminalia catappa L.) bark, manumpang (Loranthus globulus Jacq) bark, tanduk rusa stems, kayu gimto (Ligodyum sp) roots, rumput balsam (Polygala paniculata L.) roots, and cakar kucing (Acalypha indica L) roots. The leaves of luhu (Crotalaria retusa L) and kehung-kehung (Crotalaria striata Dc) containing steroids and tannins. As many as 9 out of 12 n-butanol extracts afforded toxicity efficacy against larvae of Artemia salina Leach which was confirmed through the LC₅₀ value, i.e. bellow 1000 ppm. Further, the least LC₅₀ value was achieved using the petroleum eter-extract kehung-kehung (Crotalaria striata Dc) leaves, i.e. 68.33 ppm, whereby that value approached the effectiveness standard for bioactive compounds to fight against the cancer cell, which was based on the United States National Cancer Institute.